Oral Health Conditions of Older People: Focus on the Balkan Countries - Chatzopoulos Georgios S. (Balkan Stomatological Society, 2015)
Oral health plays a pivotal role in general health, especially in older people. Oral diseases may affect the development of systemic conditions, such as diabetes mellitus, cardiovascular disease, stroke and hypertension. The most important oral health conditions that have been recorded in dental literature for older population include tooth loss, dental caries, periodontal diseases, xerostomia (dry mouth) and oral cancer. Edentulism influences social life, either causing aesthetic problems or affecting functional abilities, such as speaking, chewing and eating. Dental caries in older people is similar to that in people in their thirties. Socio-economic status and living area play a key role in the development of dental caries. In addition, the accumulation of several risk factors, such as plaque or systemic diseases, acts synergistically in the onset of periodontal disease in seniors. Furthermore, older people, mainly due to their medications, exhibit a reduced amount of saliva. Xerostomia causes difficulties in chewing, speaking and swallowing, and it has a substantial impact on older people's lives. The prevalence of oral cancer is 1-10 per 100,000 patients, and several factors (smoking, alcohol, education, economic status) play crucial role. Limited data exists today that evaluates oral health conditions of seniors in the Balkan countries. Aging and socio-economic status of seniors in the Balkans are significantly associated with oral health problems.